Penyuluhan dan Demonstrasi Pilates untuk Physical Wellness Wanita Produktif di Gereja Marjuk Bandung - Ika Rahman; Sri Gunda Fahriana Fahruddin; Lona Thesalonika; Angelika Wirani (NuCSJo : Nusantara Community Service Journal, 2025)
Productive-aged women in Indonesia face physical health challenges, such as low physical activity levels and increasing obesity prevalence. This community service program aims to enhance the physical wellness of productive-aged women in the Marjuk Church of Christ Movement, Bandung, through Pilates education and demonstration. Methods included educational sessions to increase awareness, practical training, demonstrations, and continuous mentoring. The results showed a significant improvement in participants' knowledge about the benefits of Pilates, frequency of physical activity, and physical fitness, including core strength, flexibility, and endurance. Additionally, participants reported mental benefits such as stress reduction and increased motivation for regular exercise. In conclusion, this program effectively improved participants’ awareness, skills, and physical and mental health while strengthening social solidarity within the church community. Similar programs can be expanded to other communities to extend its benefits